Responding to Molefe's Anti-abortionism - Alhadeff, Brooke; Lerm, Jessica (Theoria (Pietermaritzburg), 2025)
In his recent book, An African Ethics of Personhood and Bioethics: A Reflection on Abortion and Euthanasia (2020), South African philosopher Motsamai Molefe argues for the impermissibility of abortion on the grounds that a foetus possesses the potential for dignity, which he argues amounts to the potential to develop the African virtues. However, we argue, firstly, that his account of the supposed wrongfulness of abortion is inconsistent with his later account of the supposed permissibility of euthanasia; we argue that his account succumbs to the well-known objections to the potentiality principle from as long ago as the 1970s; and, finally, we argue that his account is indeterminate in so far as it does not conclusively entail the immorality of abortion in the first place. Altogether, this amounts to a decisive rejection of Molefe's anti-abortionism.